To solve the equation, factor x^2-6x-16 utilizing formula x^2+left(a+b ight)x+ab=left(x+a ight)left(x+b ight). To find a and also b, set up a mechanism to be solved.

You are watching: What is the factored form of x2 – 6x – 16?

Since ab is negative, a and b have actually the the opposite signs. Since a+b is negative, the negative number has greater absolute value than the positive. List all together integer bag that offer product -16. x2-6x-16=0 Two options were uncovered : x = 8 x = -2 step by action solution : step 1 :Trying to variable by splitting the center term 1.1 Factoring x2-6x-16 The an initial term is, x2 that is ...
2x2-6x-16=0 Two solutions were found : x =(3-√41)/2=-1.702 x =(3+√41)/2= 4.702 action by action solution : step 1 :Equation in ~ the end of action 1 : (2x2 - 6x) - 16 = 0 step 2 : action 3 ...
3x2-6x-16=0 Two services were discovered : x =(6-√228)/6=1-1/3√ 57 = -1.517 x =(6+√228)/6=1+1/3√ 57 = 3.517 step by step solution : action 1 :Equation at the end of step 1 : (3x2 - 6x) - 16 = 0 ...
-3x2-6x-16=0 Two remedies were uncovered : x =(6-√-156)/-6=1+i/3√ 39 = -1.0000-2.0817i x =(6+√-156)/-6=1-i/3√ 39 = -1.0000+2.0817i step by step solution : step 1 :Equation at the end of step 1 ...
2x2-6x-1=0 Two options were uncovered : x =(6-√44)/4=(3-√ 11 )/2= -0.158 x =(6+√44)/4=(3+√ 11 )/2= 3.158 action by step solution : step 1 :Equation in ~ the end of action 1 : (2x2 - 6x) - 1 = 0 ...
2x2-6x-6=0 Two solutions were found : x =(3-√21)/2=-0.791 x =(3+√21)/2= 3.791 action by step solution : action 1 :Equation at the finish of action 1 : (2x2 - 6x) - 6 = 0 action 2 : step 3 ...
More Items     To deal with the equation, variable x^2-6x-16 making use of formula x^2+left(a+b ight)x+ab=left(x+a ight)left(x+b ight). To uncover a and also b, set up a system to it is in solved.
Since abdominal is negative, a and also b have the the opposite signs. Due to the fact that a+b is negative, the negative number has higher absolute value than the positive. Perform all together integer bag that give product -16.
To deal with the equation, element the left hand next by grouping. First, left hand side needs to it is in rewritten as x^2+ax+bx-16. To discover a and also b, set up a device to be solved.
Since ab is negative, a and also b have actually the opposite signs. Due to the fact that a+b is negative, the an adverse number has better absolute worth than the positive. Perform all together integer pairs that give product -16.
All equations that the form ax^2+bx+c=0 can be fixed using the quadratic formula: frac-b±sqrtb^2-4ac2a. The quadratic formula offers two solutions, one as soon as ± is addition and one once it is subtraction.
This equation is in standard form: ax^2+bx+c=0. Substitute 1 for a, -6 for b, and also -16 for c in the quadratic formula, frac-b±sqrtb^2-4ac2a.
Quadratic equations such as this one have the right to be solved by perfect the square. In order to complete the square, the equation must first be in the kind x^2+bx=c.
Divide -6, the coefficient of the x term, by 2 to get -3. Then include the square of -3 come both political parties of the equation. This step makes the left hand next of the equation a perfect square.
Factor x^2-6x+9. In general, when x^2+bx+c is a perfect square, that can always be factored as left(x+fracb2 ight)^2.

See more: How Far Is Kissimmee From Daytona Beach, Fl To Kissimmee, Fl

Quadratic equations such as this one deserve to be solved by a brand-new direct factoring technique that walk not call for guess work. To use the straight factoring method, the equation must be in the kind x^2+Bx+C=0.
Let r and s it is in the determinants for the quadratic equation such the x^2+Bx+C=(x−r)(x−s) where sum of factors (r+s)=−B and the product of components rs = C
Two number r and s amount up come 6 exactly when the average of the two numbers is frac12*6 = 3. Girlfriend can also see that the midpoint the r and also s corresponds to the axis of the opposite of the parabola stood for by the quadratic equation y=x^2+Bx+C. The worths of r and s space equidistant from the center by one unknown amount u. To express r and s v respect to variable u.  EnglishDeutschEspañolFrançaisItalianoPortuguêsРусский简体中文繁體中文Bahasa MelayuBahasa Indonesiaالعربية日本語TürkçePolskiעבריתČeštinaNederlandsMagyar Nyelv한국어SlovenčinaไทยελληνικάRomânăTiếng Việtहिन्दीঅসমীয়াবাংলাગુજરાતીಕನ್ನಡकोंकणीമലയാളംमराठीଓଡ଼ିଆਪੰਜਾਬੀதமிழ்తెలుగు